Resistencia y elasticidad a la flexión de la guadua angustifolia kunth de Pitalito, Huila (2018)
Ultimate strength and flexural modulus of elasticity were evaluated in samples of Guadua angustifolia Kunth from the municipality of Pitalito, Huila. From obtaining samples to testing, the recommendations of the Colombian Technical Standard NTC 5300, Harvest and post-harvest of the culm of Guadua angustifolia Kunth, NTC 5525, Test methods for the determination of physical and mechanical properties of the Guadua angustifolia Kunth and the NSR 10 “Reglamento Colombiano de Construcciones Sismo Resistente” Chapter G “Estructuras de madera y estructuras de guadua” were followed. The values of the allowable stress and the modulus of elasticity of 13.85 MPa and 15483 MPa, respectively, were found, for average moisture content of 102 %. Additionally, comparisons with other investigations carried out in Colombia were made.